Complexos de rutênio com ligantes de interesse biológico: aspectos químicos, estruturais e avaliação de suas atividades biológicas - Corrêa, Rodrigo de Souza (Universidade Federal de São Carlos, 2013)
This thesis focus on the synthesis, characterization and evaluation of the biological properties of three series of phosphinic ruthenium complexes containing bioligands of purine and pyrimidine derivatives. Series 1: [RuCl(alo)(dppb)(bipy)]PF6, [RuCl(alo)(dppb)(bipy)] Cl, [RuCl(alo)(dppb)(4mebipy)]PF6, [RuCl(alo)(dppb)(5mebipy)]PF6, [RuCl(Im) (dppb)(bipy)]PF6, [RuCl(Bzm)(dppb)(bipy)]PF6, [RuCl2(alo)2(dppb)], [RuCl2(alo)2 (PPh3)2] and [RuCl3(alo)(dppb)], where alo = allopurinol, Im = imidazole, benzimidazole Bzm =, bipy = 2,2'-bipyridine, 4mebipy = 4,4'-dimethyl-2,2 '-bipyridine, 5mebipy = 5,5'-dimethyl-2, 2'- bipyridine, PPh3 = triphenylphosphine and dppb = 1,4-bis (diphenylphosphino)butane. Series 2: [Ru(tim)(dppb)(bipy)]PF6 and [Ru(cit)(dppb)(bipy)]ClO4, trans- [Ru(PPh3)2(5FU)(bipy)]PF6, trans-[Ru(PPh3)2(tim) (bipy)]PF6 and trans- [Ru(PPh3)2(CTD)(bipy)]ClO4, where tim = thymine, cit = cytosine, 5-FU = 5-fluorouracil, CTD = cytidine . Series 3: cis-[Ru(PPh3)2(2TU)2], cis-[Ru(PPh3)2(6m2TU)2], [Ru(2TU)2(dppb)] and [Ru(6m2TU)2(dppb )], trans-[Ru(PPh3)2(2TU)(bipy)]PF6 and trans- [Ru(PPh3)2(6m2TU)(bipy)]PF6, [Ru(2MT)(dppb) (bipy)]PF6, cis-[Ru(PPh3)2(2MT)2] and trans-[Ru(PPh3)2(2MT)(bipy)]PF6. (2TU = 2-thiouracil; 6m2TU = 6-methyl-2-thiouracil, 2MT = mercaptothiazoline). These compounds were characterized by 31P{1H} 13C and 1H nuclear magnetic resonance and by cyclic voltammetry and differential pulse, conductometry, absorption spectroscopy in the infrared region, elemental analysis, mass spectrometry and Xray diffraction, and absorption spectroscopy in the UV/Vis which has assisted the spectroscopic study of DNA interactions. The interaction constants (Kb) values are in the range of 103-104 M-1, suggesting a weak interaction between the complex and DNA (noncovalent). Cationic compounds with regions suitable to be involved hydrogen bonding present greater interaction constant (104 M-1) than the neutral complexes and with less possibility of intermolecular bonds. The complexes were also evaluated, in vitro, against breast cancer cells (MDA-MB-231 and MCF-7), as well as fibroblasts cells (L-929). It was observed that the compounds of the series 1 and 2 are more selective against tumor cells than the complexes of series 3. In addition, the compounds of series 1 were also tested against xanthine oxidase, an enzyme which is directly involved in the gout disease. The complexes RuCl(alo)(dppb)(bipy)]PF6 (IC50 = 2.2 μM), [RuCl(alo)(dppb)(4mebipy)]PF6 (IC50 = 2.8 μM) and [RuCl(alo)(dppb)(5mebipy)]PF6 (IC50 = 0.75 μM) are more active than free allopurinol (IC50 = 4.2 μM), showing that the coordination of allopurinol enhances the effect of the drug. Also, series 1 and compounds with 2MT were evaluated against the T. cruzi parasite (trypomastigote) in order to screening their potential against Chagas' disease. The [RuCl(alo)(dppb)(4mebipy)]PF6 (IC50 = 1.87 μM), [Ru(2MT)(dppb)(bipy)]PF6 (IC50 = 0.16 μM) and trans-[Ru(PPh3)2(2MT)(bipy)]PF6 (IC50 = 0.011 μM) complexes were the most active ones, in which the last one is 1000-fold better than the benznidazole drug (IC50 = 10.6 μM).
Ruthenium complexes with ligands of biological interest: Chemical and Structural aspects and evaluation of their Biological Activities
Keywords: Química inorgânica; Complexos de rutênio; Bioligantes; Agentes antineoplásicos; Agentes antigota; CIENCIAS EXATAS E DA TERRA::QUIMICA